WATER MASS ANALYSIS OF THE INDONESIAN THROUGHFLOW BY MEANS OF PRINCIPLE COMPONENT ANALYSIS - Yuli Naulita (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2007)
The water masses in both routes of Indonesia Throughflow (ITF) from historical hydrographic data are examined by means of the Principal Component Analysis (PCA), a multivariate statistical technique, during the southeast monsoon and northwest monsoon, and compared with the TS diagrams. The temperature and dissolves oxygen always play in the same PC, which describeds a variability contribution of the water mass characters, while salinity in a different PC. The relationship of the water masses parameters may indicate the character of dissolved oxygen as a non-conservation tracer. The Principle Component Analysis may also be used to follow the trendds of core layer attenuation as verified by the salinity corresponds at the PC. It will be higher with S-max and S-min and more closely resemble the sources. This condition is shown in the waters close to the main sources in the Pacific, like Sulawesi, Malkuku and Halmahera Sea, where both the salinity extrema can still be observed. Conversely, in the Banda and Timor Sea, where S-max and S-min are greatly attenuated even completely remove, the correspondence of salinity in the water mass character variability becomes smaller. As seen on TS and TO diagrams, PCA graphics are also showed the dominant of the north Pacific water in the western route seas, the Sulawesi, Makasar Strait and the Florest Sea, but relatively salty water of South Pacific origin is observed in the Halmahera Sea, particularly in the northwest monsoon. The strong seasonal variablity of surface water in the Indonesian can also be observed in the PCA graphics. Keywords: Water Mass, Indonesian Throughflow, PCA.